2012
DOI: 10.15376/biores.7.3.3711-3719
|View full text |Cite
|
Sign up to set email alerts
|

Properties of parallel strand lumber from two hybrid poplar clones using melamine urea formaldehyde adhesive

Abstract: Experimental parallel strand lumbers (PSLs) were manufactured from fast growing rotary peeled I-214 (Populus x euramericana) and I-77/51(Populus deltoides) hybrid poplar clones veneer strands with melamine urea formaldehyde (MUF) adhesive. The results showed that hybrid poplar clones can be used in PSLs manufacturing. Physical and mechanical properties of PSLs were affected by clone types. The I-77/51 clone had better properties and was found to be more suitable for PSLs manufacturing compared to the I-214 clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to the data obtained, it was determined that there was a statistically significant (P-value < 0.05) difference between the 2-h and 24-h water absorption percentage values of the samples prepared with polyol-added adhesive. The data obtained were in agreement with previous studies (Kurt and Cavus 2011;Kurt et al 2012Kurt et al , 2013.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…According to the data obtained, it was determined that there was a statistically significant (P-value < 0.05) difference between the 2-h and 24-h water absorption percentage values of the samples prepared with polyol-added adhesive. The data obtained were in agreement with previous studies (Kurt and Cavus 2011;Kurt et al 2012Kurt et al , 2013.…”
Section: Resultssupporting
confidence: 93%
“…Statistically, polyol-added adhesive has a decreasing effect on impact strength. The impact resistance of parallel-strand lumber produced with different wood species obtained in previous studies showed a better performance than the dynamic bending resistance of the lumber from which it was produced (Wu et al 1998;Simpson et al 1999;Sulastiningsih and Santoso 2005;Kurt and Cavus 2011;Ahmad and Kamke 2011;Kurt et al 2012Kurt et al , 2013Li et al 2015;Gong et al 2016;He et al 2018;Zhang et al 2018). The load-deformation graphs obtained during the screw-holding capacity test are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation